Analisis Implementasi Sistem Pengendalian Internal Untuk Mencegah Kredit Macet Pembiayaan Musyarakah Modal Kerja (Studi Kasus Bank Syariah Indonesia Kcp Kisaran) - Alicia, Febi; Atika, Atika; Yanti, Nursantri (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2025)
This study aims to avoid the emergence of bad debts and to optimize the credit distribution system, therefore it is necessary to implement a good internal control structure for the credit function. The method used in this study is qualitative research with a phenomenological approach and case studies. Data obtained from interviews and documentation through informants consisting of the Operational Manager of BSI KCP Kisaran, with the presence of 5 C (Character, Capacity, Capital, Conditions of money and Collateral). The results of the study that BSI KCP Kisaran does not use theory but uses an object system that will be measured by the Internal Control System. This study is expected to prevent bad debts in MUSYARAKAH working capital financing The Importance of Comprehensive Risk Assessment A comprehensive assessment of the risk of bad debts is very important to minimize the risk of   loss for financial institutions. By considering all relevant factors, financial institutions can make better credit decisions and build a healthy credit portfolio To prevent bad debts and optimize the credit distribution system, an effective internal control structure (SPI) is needed for the credit function